DETERMINANT OF THE BEHAVIOR OF KADARZI (NUTRITION AWARE FAMILIES) IN TODDLER MOTHERS AT WORK AREA OF THE REUBEE HEALTH CENTERS, DELIMA DISTRICT, PIDIE REGENCY - Arbi, Anwar; Ariska, Tasya; Liana, Intan; Zakaria, Radhiah; Agustina, Agustina (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2022)
Background: Kadarzi (Nutrition Aware Families are families with balanced nutritional behavior that who are able to recognize, prevent and overcome nutritional problems in every member of their family. Families are said to have good Kadarzi behavior if they have implemented the five Kadarzi indicators, weigh themselves regularly, give exclusive breastfeeding, eat a variety of foods, use iodized salt and consume nutritional supplement. The national target for nutrition-conscious families is 80%. Reubee Community Health Center, of the five indicators of Kadarzi, two indicators that have not reached the target are exclusive breastfeeding (75%) and the indicator of using iodized salt is only 12%. Methods: This research is descriptive analytic with a cross sectional design. Univariate and bivariate data analysis with Chi Square test. Results: Research showed that there was a relationship between knowledge (p value=0.001), family income (p value=0.004), with levels of Kadarzi behavior of mothers with toddlers and there was no relationship between husband's support (p value=0.288) and the behavior of Kadarzi of toddlers mothers. Recomendation: To the Reubee Health Centers staffs to be able to increase counseling activities about the importance of implementing the Nutrition Awareness-Family for mothers of toddlers in the working area of Community Health Centers, in order to increase their knowledge of toddlers nutritional healt.